Genetic divergence and physiological quality of dwarf castor bean lines seeds1 - Oliveira Neto, Sebastião Soares de [UNESP]; Ramos, Andréia Rodrigues [UNESP]; Oliveira, Carlos Eduardo da Silva [UNESP]; Silva, Edvaldo Aparecido Amaral da [UNESP]; Zanotto, Maurício Dutra [UNESP] (FapUNIFESP (SciELO), 2022)
The development of new castor bean genotypes with high grain yield and physiological seed quality is fundamental to the economic success of the crop. This study aimed to evaluate the agronomic performance and physiological quality of seeds of twelve castor bean lines, in order to determine superior genotypes. Plant height, insertion height and number of racemes, grain yield, oil content, germination percentage and vigor were evaluated. The dwarf castor bean lines H4, H5 and H11 were responsible for a grain yield above 1,400 kg ha-1 and are, therefore, promising for getting new hybrids. The indirect selection of dwarf castor bean lines can be performed through morphologic traits. The lines H4, H6, H9, H11 and H12 produced seeds with superior vigor and germinative quality.
Keywords: castor bean breeding; Ricinus communis L; seed quality